Integrating climate security into policy frameworks: Jordan - McMurray, Spencer; Rüttinger, Lukas; Schapendonk, Frans; Jaskolski, Martina; Saleh, Rana (2023)
The climate crisis is increasing security risks in Jordan. Of the manifold risks Jordan must contend with, most pressing are those with direct implications for water resources which are already under significant strain due to both climatic and human-induced factors. Higher temperatures are leading to more evapotranspiration and reduced rainfall are especially critical, straining the groundwater and aquifer reserves that are already over exploited. Extreme weather events and their impacts, including droughts, flash floods, and landslides, further complicate matters. These risks translate into important implications for Jordanians across a variety of areas, including political, social, demographic and economic realms, especially when combined with pre-existing grievances and especially poverty. This roadmap outlines a set of specific mechanisms and opportunities for the integration of climate, peace, and security considerations into policy and legislative frameworks in Jordan.